2020
DOI: 10.1016/j.puhe.2020.09.016
|View full text |Cite
|
Sign up to set email alerts
|

Socio-economic status and COVID-19–related cases and fatalities

Abstract: Objectives The United States has the highest number of Coronavirus Disease 2019 (COVID-19) in the world, with high variability in cases and mortality between communities. We aimed to quantify the associations between socioeconomic status and Coronavirus Disease 2019 (COVID-19) related cases and mortality in the U.S. Study Design: Nationwide COVID-19 data at the county level that was paired with the Distressed Communities Index (DCI) and its component metrics of socioeco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

33
302
5
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 371 publications
(348 citation statements)
references
References 17 publications
33
302
5
8
Order By: Relevance
“…Furthermore, these crowded markets are often located within pockets of poverty, suggesting that the socioeconomic dynamics of localities might have influenced how the virus spread through communities. The findings support previous research (Hamidi et al, 2020;Hawkins et al, 2020;, which have established that socioeconomic factors play an important role in COVID-19 prevalence in the USA. We computed and mapped the mean monthly mobility levels from GCMR data for grocery and pharmacy-related trips to corroborate the model results.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, these crowded markets are often located within pockets of poverty, suggesting that the socioeconomic dynamics of localities might have influenced how the virus spread through communities. The findings support previous research (Hamidi et al, 2020;Hawkins et al, 2020;, which have established that socioeconomic factors play an important role in COVID-19 prevalence in the USA. We computed and mapped the mean monthly mobility levels from GCMR data for grocery and pharmacy-related trips to corroborate the model results.…”
Section: Discussionsupporting
confidence: 91%
“…Individuals with SMD may be particularly vulnerable because SMD in itself and its co-morbidities are likely associated with lower socioeconomic status ( 57 ). This would be consistent with findings from the US that COVID-19 mortality is more frequent in lower socioeconomic ethnic minority groups ( 60 , 61 ). The impact of socioeconomic status and ethnicity on the risk of COVID-19 infection and mortality in individuals with SMD requires further study.…”
Section: Psychosocial Stresssupporting
confidence: 92%
“…Similar ecological studies showed that areas with lower socioeconomic status were related with higher rates of COVID-19 transmission, as well as mortality ( 5 , 6 ). These results were also replicated in population-based studies ( 7 , 8 ).…”
Section: Introductionmentioning
confidence: 59%